Four new species of Euodynerus Dalla Torre, 1904 (Hymenoptera: Vespidae: Eumeninae) from China, with a key to the Chinese species - Ma, Zhenxia; Chen, Bin; Li, Tingjing (Zootaxa, 2017)
Four new species, namely E. (Euodynerus) carinatus sp. nov. (Sichuan), E. (Pareuodynerus) deqinensis sp. nov. (Yunnan), E. (P.) ferrugineus sp. nov. (Yunnan), and E. (P.) similinipanicus sp. nov. (Yunnan), are described and illustrated. Euodynerus (P.) strigatus (Radoszkowski) is newly recorded from China. A key to the Chinese species of Euodynerus is given.